2007
DOI: 10.1007/s00586-007-0479-7
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness evaluation of an RCT in rehabilitation after lumbar spinal fusion: a low-cost, behavioural approach is cost-effective over individual exercise therapy

Abstract: Recently, Christensen et al. reported the clinical effects of a low-cost rehabilitation program equally efficient to a relatively intensive program of individual, physiotherapist-guided exercise therapy. Yet, the low-cost approach is not fully supported as an optimal strategy until a full-scale economic evaluation, including extra-hospital effects such as service utilization in the primary health care sector and return-to-work, is conducted. The objective of this study was to conduct such evalution i.e. invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Similar results on cost-effectiveness were reported when a biopsychosocial postoperative rehabilitation intervention was utilized following lumbar fusion surgery, relative to standard post-operative care (Sogaard, Bunger, Laurberg, & Christensen, 2008). The interdisciplinary rehabilitation group had a significantly greater, and constant, probability of being cost-effective in terms of improved pain and disability scores compared to the usual-care group.…”
Section: Cost-effectiveness Of Biopsychosocial Pain Interventionssupporting
confidence: 57%
“…Similar results on cost-effectiveness were reported when a biopsychosocial postoperative rehabilitation intervention was utilized following lumbar fusion surgery, relative to standard post-operative care (Sogaard, Bunger, Laurberg, & Christensen, 2008). The interdisciplinary rehabilitation group had a significantly greater, and constant, probability of being cost-effective in terms of improved pain and disability scores compared to the usual-care group.…”
Section: Cost-effectiveness Of Biopsychosocial Pain Interventionssupporting
confidence: 57%
“…A study published in 2003 compared the effect of three different postoperative rehabilitation programs initiated 3 months after LSF. They found that groupbased intervention deploying a bio-psycho-social approach outperformed video instruction and intensive physiotherapy [2,6]. A study published in 2010 documented the superiority of a psychomotor therapy intervention focusing on cognition, behaviour and motor relearning activated 3-12 weeks after LSF [1].…”
Section: Introductionmentioning
confidence: 99%
“…The conclusions could even be reverted when patients undergoing rehabilitation instead of surgery require secondary surgery. Similarly, we should consider the cost-effectiveness of the type of post-surgical rehabilitation as investigated by Soegaard et al [78].…”
Section: Cost-effectiveness Studiesmentioning
confidence: 99%